PENGARUH ROA, CR, DAN TATO TERHADAP HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA PERIODE 2021-2023 - Sulistiyowati, Novi; Wahyuni, Ika; Nanggala, Ardhya Yudistira Adi (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to examine the effect of Return On Assets (ROA), Current Ratio (CR), and Total Asset Turnover (TATO) on Stock prices through Capital structure in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The method used in this study is quantitative. The sample consisted of eleven companies selected by purposive sampling from a total population of 73. Data were obtained from the company’s annual financial reports, which are available on the official IDX website. Data analysis used the Partial Least Square (PLS) analysis technique through SmartPLS software version 3.0. The study results show that ROA and TATO do not have a significant effect on Capital structure or Stock price, while CR has a significant negative effect on both. This research also found that Capital structure significantly negatively affects Stock prices. Indirectly, CR significantly positively affects Stock price through Capital structure, while ROA and TATO do not show a significant mediation effect.